The Relevance of Mathematical Critical Thinking Skill with Numerical Intelligence and Learning Independence - Imam Suseno; Mamik Suendarti; Supeno Supeno; Yeyen Suhendar (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2023)
Several studies show point out the ability of mathematical critical thinking of Indonesian students is still low, students often have difficulty dealing with situations that require problem-solving skills using Mathematics. Through a survey method, this research seeks to reveal the causal relationship between variables, namely whether the students’ mathematical critical thinking skills of SMAN Serang Regency, West Java are influenced by numerical intelligence and are also influenced by students’ learning independence. The research targets were class X students from SMAN 1 Anyar, SMAN 1 Mancak, and SMAN 1 Gunungsari which are in Serang Regency, West Java. A total of 88 students as respondents or research samples were selected using the proportional cluster random sampling technique. Data collection on students' mathematical critical thinking skills were used as an instrument for essay tests, data on students' numerical intelligence was used as a multiple choice test instrument, and learning independence was obtained by distributing a questionnaire. The results of the research show that there is an influence of numerical intelligence and learning independence partially and/or jointly on the students’ mathematical critical thinking skills of SMAN Serang Regency. Students' mathematical critical thinking skills can be improved by optimizing internal and external factors within themselves. Through fun Mathematics learning activities, prioritizing the scientific method approach in solving mathematical problems, as well as increasing awareness of learning independence by utilizing other sources of learning Mathematics besides from the teacher. In addition, seeking a positive attitude of students towards the importance of Mathematics learning to continue to be appropriately organized.